Implementation of School-Based Management in Improving the Quality of Education at MTs N 1 Padangsidimpuan - Marpaung, Wardatun Thaibah; Marpaung, Dian Pratiwi Br.; Nasution, Inom (Yayasan Pendidikan Islam Akmalia, 2023)
Abstract : In accordance with the Law of the Republic of Indonesia Number 14 of 2005 concerning Teachers and Lecturers Article 2 paragraph (1) confirms that teachers have a position as professionals at the level of basic education, secondary education, and early childhood education in the formal education pathway appointed in accordance with regulations legislation. Article 10 paragraph (1) states that